2012
DOI: 10.2215/cjn.12791211
|View full text |Cite
|
Sign up to set email alerts
|

Design of Clinical Trials in Acute Kidney Injury

Abstract: SummaryAcute kidney injury (AKI) remains a complex clinical problem associated with significant short-term morbidity and mortality and lacking effective pharmacologic interventions. Patients with AKI experience longer-term risks for progressive chronic ESRD, which diminish patients' health-related quality of life and create a larger burden on the healthcare system. Although experimental models have yielded numerous promising agents, translation into clinical practice has been unsuccessful, possibly because of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
121
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 135 publications
(124 citation statements)
references
References 38 publications
1
121
0
1
Order By: Relevance
“…The second aim of our study was to determine the incidence of MAKE, MACE, and MARCE, because these are proposed composite endpoints of clinical trials (14,15). Our analysis showed that patients who experienced an episode of AKI were at significant risk for death and permanent loss of renal function.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second aim of our study was to determine the incidence of MAKE, MACE, and MARCE, because these are proposed composite endpoints of clinical trials (14,15). Our analysis showed that patients who experienced an episode of AKI were at significant risk for death and permanent loss of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, poor outcomes associated with AKI exceed those of an MI, a disease that carries a much higher public health profile, and whose prevention attracts very high levels of government and nongovernment funding. We also propose that composite endpoints (MAKE, MACE, and MARCE) be used in future clinical trials of AKI, because they provide a method that improves the ability to detect meaningful differences in therapeutic interventions (14)(15)(16). Finally, improved prevention and therapy of AKI, as well as follow-up surveillance of this high-risk group, are urgently required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…80 The vast majority of successful preclinical experiments to date have been prophylactic, with exposure to the protective agent before an ischemic, septic, or nephrotoxic insult. 81 Fewer experimental models also include early postinsult exposures, which in some cases are successful. However, a major weakness of current preclinical experimental AKI models is that they do not routinely incorporate a more delayed secondary prevention/therapeutic component, with late addition of therapy when AKI is already developing.…”
Section: What Are the Clinical Correlates Of These Animal Models In Hmentioning
confidence: 99%
“…However, following the lead of Devarajan and others [3] who have pioneered the use of urinary biomarkers in the diagnosis of acute kidney injury, I would suggest that investigators work together to develop a panel of suitable biomarkers that can be combined in an array and tested simultaneously in a single assay to enhance the sensitivity and specificity of these analytes in patients with new-onset primary nephrotic syndrome. Such an approach would be a welcome addition to the management of children and adolescents with this important clinical problem.…”
mentioning
confidence: 99%